Efficiency and risks of selenite combined with different water conditions in reducing uptake of arsenic and cadmium in paddy rice. (July 2020) - Lv, HaiQin; Chen, WenXiang; Zhu, YanMing; Yang, JiGang; Mazhar, Sohaib H.; Zhao, PingPing; Wang, LiZhen; Li, YuanPing; Azam, Syed Muhammad; Ben Fekih, Ibtissem; Liu, Hong; Rensing, Christopher; et al.
Abstract: The co-contamination of arsenic (As) and cadmium (Cd) in soils is a common problem. Selenium (Se) can reduce the uptake of As and Cd in plants, and in practice, the alternate wetting and drying is a common culture mode in rice production. However, it is unknown whether Se can efficiently reduce As and Cd concentrations in crops suffering from a high-level contamination of As and Cd under different soil water conditions. In this study, we assessed the efficiency and risks of selenite [Se(IV)], in a pot experiment, to reduce the uptake of As and Cd in a rice plant (YangDao No 6) growing in a heavily contaminated soil by As and Cd (pH 7.28) under different soil water conditions. The results showed that Se(IV) failed to control the grain total As and Cd concentrations within their individual limited standard (0.2 mg kg −1 ) despite that Se(IV) significantly reduced the grain total As and Cd concentrations. The soil drying treatment alone could reduce the accumulation of arsenite [As(III)] in the grains, but additional Se(IV) stimulated the accumulation of As(III) in the grains under soil drying conditions. In addition, the addition of Se(IV) enhanced the As and Cd concentrations in the shoots and/or roots of rice plants under certain conditions. The above results all suggested that the utilization of Se(IV) in a high contaminated soil by As and Cd cannot well control the total concentrations of As and Cd in plants. In this study, the available concentrations of As and Cd in the rhizosphere soil, the rhizosphere soil pH, the formation of root iron/manganese plaques and the concentrations of essential elements in the grains were monitored, and the related mechanisms on the changes of these parameters were also discussed. This study will give a guideline for the safe production of rice plants in a heavily co-contaminated soil by As and Cd. Graphical abstract: Image 1 Highlights: Se(IV) decreased grain total As/Cd concentrations under different conditions. But Se(IV) failed to control grain total As/Cd below their safe limitation. Soil drying for 10d plus 5 mg kg −1 Se(IV) did best to control grain As/Cd levels. Soil drying plus Se(IV) stimulated the yield by enhancing hundred-grain weight. Se(IV) stimulated grain As(III) accumulation under field drying conditions.